Insecticidal Activity of Gamal (Gliricidia sepium) Leaf Extracts Against the Darkling Beetle Alphitobius diaperinus - Widiyaningrum, Priyantini; Nur, Wibowo Faria Fadillah; Indriyanti, Dyah Rini; Setiati, Ning (Universitas Negeri Semarang, 2024)
Alphitobius diaperinus is a well-known insect pest in broiler farms. Larvae and adults of A. diaperinus act as disease vectors for poultry, and their presence has the potential to increase the risk of carcass contamination in slaughterhouses. Chemical insecticide control is still considered ineffective and environmentally unfriendly. Plant-based insecticide formulations offer a more environmentally friendly approach to pest control compared to chemical insecticides. The ethanol extract of Gamal leaves was tested on the darkling beetle A. diaperinus to determine its insecticidal activity. Five pairs of A. diaperinus were treated at five levels of extract concentration and then maintained in an insect container with wheat bran (pollard) food for 5 weeks. The insecticidal efficacy was measured based on the difference in mortality in the toxicity test and the reproductive ability of adult A. diaperinus by counting the number of larvae produced during the rearing period. The results showed that differences in extract concentrations significantly affected toxicity and the number of larvae produced. The more concentrated the extract, the higher the insect mortality, with the estimated LC50 value of the extract being 20.80% concentration within 72 hours. Reproductive ability showed that the higher the concentration of the extract, causing a decrease in the number of larvae produced, with the optimum concentration found in the 80% treatment. Thus, Gamal leaf extract has potential as a botanical insecticide for biological control of A. diaperinus pest.